Acute Fetal Anemia Diagnosed by Middle Cerebral Artery Doppler Velocimetry in Stage V Twin-Twin Transfusion Syndrome - Jennifer Salcedo; Esther Friedrich; Deborah A. Wing; Manuel Porto (Thieme Medical Publishers, Inc., 2011)
In stage V twin-twin transfusion syndrome (TTTS), up to 50% of surviving twins die or experience permanent disabilities, likely due to acute intertwin hemorrhage resulting in sudden severe anemia of the survivor. Although fetal middle cerebral artery (MCA) Doppler studies demonstrate strong correlation with fetal hemoglobin values, acute hemorrhagic events are more difficult to diagnose, and optimal timing of delivery of the survivor poses an obstetric dilemma. We report a case of newly diagnosed stage V TTTS at 28 weeks gestation, complicated by acute severe anemia diagnosed by significantly abnormal fetal MCA Doppler studies. The anemic twin was urgently delivered and is doing well without significant sequelae.